PENGARUH BABY SPA TERHADAP KENAIKAN BERAT BADAN BAYI DI RUMAH SEHAT KITA PURWOKERTO - Wulan Margiana; Wulan Margiana; Ima Syamrotul Muflihah (Universitas Harapan Bangsa Purwokerto, 2018)
Baby Spa is one of the physiotherapy in infants and can stimulate baby motor movement. Research on term infants aged 1-3 months, who were massaged 15 minutes, 2 times a week for 6 weeks also gained 50% more weight than control (Riksani, 2012). Purpose of this study was to determine the effect of baby spa on weight gain in infants at Rumah Sehat Kita Purwokerto. Method used in this research is quasy experiment with cross sectional approach. Results showed there was a difference in infant weight gain between before the baby spa after the baby spa is done with the value of p value 0.001. So it can be concluded that baby spa effect on baby's weight gain. Keywords: Baby Spa, baby's weight gain